2021
DOI: 10.1192/bji.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders in Malaysia: an increase in lifetime prevalence

Abstract: There is an increasing prevalence of mental disorders in Malaysia, with a growing need to improve access to timely and efficient mental healthcare to address this burden. This review outlines the current legislative framework and the challenges of delivering mental healthcare and treating mental disorders in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…The Ministry of Health had allocated only 1.3% of the total health budget for mental health in 2017 and 2018. 8 This spending provision is below the World Health Organization (WHO) recommendation, 8 whereas upper-middle-income countries reported spending an average of 2.4% of their health budget on mental health.…”
Section: Mental Healthcare In Malaysiamentioning
confidence: 95%
See 3 more Smart Citations
“…The Ministry of Health had allocated only 1.3% of the total health budget for mental health in 2017 and 2018. 8 This spending provision is below the World Health Organization (WHO) recommendation, 8 whereas upper-middle-income countries reported spending an average of 2.4% of their health budget on mental health.…”
Section: Mental Healthcare In Malaysiamentioning
confidence: 95%
“…13 Malaysia has a significant lack of psychiatrists, with just 1.27 per 100 000 population. 8 This poses a massive challenge to developing and delivering an integrated service model. A study published in 2021 reported that Malaysia needs 3000 psychiatrists to meet the WHO recommendation of 10 psychiatrists per 100 000 population.…”
Section: Long-term Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the pandemic and financial pressure have been the main sources that have caused the increase in mental health problems in Malaysia. Raaj, Navanathan, Tharmaselan, and Lally (2021) emphasized how economic burden is significantly related to the increase in mental health prevalence among Malaysians. With the economic struggles, the cultural changes of rapid urbanization are one of the influential factors of various social problems including divorce, increase in alcohol and drug use, and changes in parenting methods (Raaj et al, 2021).…”
Section: Problem Statementmentioning
confidence: 99%